MOLECULAR APPROACH AND PRELIMINARY SCREENING OF CULTURABLE FREE-LIVING RHIZOBIUM AS PLANT GROWTH ENHANCER - Sulistiyani, Tri Ratna; Meliah, Siti; Masrukhin; Mia Kusmiati; Agus Budiyanto; Dwi Agustiyani Muslichah (Malaysian Journal of Science, 2024)
The population increase and changes in consumption are the main challenges in agriculture production related to the increase in basic needs, especially food. The high demand for food leads to fertilizer application to effectively speed up and manage plant growth. The search for alternative biofertilizers from unique microorganisms is needed to tackle this issue. Rhizobium is known as a plant growth enhancer. In this study, they were isolated from Aek Natonang, famous as “the lake above the lake”, located on Samosir Island, North Sumatra, at more than 1400 m. These geographical conditions offer various potential unique microorganisms. The collected free-living Rhizobium from the sample was identified by morphological characteristics and molecular approach through 16S rDNA sequence. They were assessed for their abilities as plant growth promoters. Based on the morphological characterization, they showed a creamy yellow colony, excessive mucus production, Gram-staining negative, and catalase positive. Through the molecular approach, they have 98-100% similarity with Rhizobium sp.. A combination of morphological and molecular approaches strengthens the identification results. Six Rhizobium sp. produced IAA, siderophore, ACC Deaminase, and ammonia. They could also solubilize phosphate tolerated to high pH and salt concentrations. All the collected Rhizobium were qualitatively potential to enhance the plant growth. They performed diverse abilities in vitro, and Rhizobium radiobacter strain DT 14.16 displayed the best features. Hence, they can be a candidate for biofertilizer. However, none of the collected Rhizobium could suppress the growth of Ralstonia solanacearum. Using quality indigenous bacteria such as Rhizobium, is an environmentally friendly technology to increase agricultural productivity and hopefully provide better yield.